(untitled) (Journal of Social Sciences Review, 2023)
Invention and creativity are always driven by intellectual property rights (IPRs). Additionally, it boosts competitiveness among nations and generates new employment opportunities. The work of authors, artists, inventors, architects, and other IPR users is protected and benefited by IPR. After all, both developed and developing countries face significant difficulties when it comes to preserving intellectual property. The protection of the intellectual property is provided by several international laws. A number of principles are used by international law to affirm the protection of intellectual property. In addition, most nations have their own laws in place to safeguard their intellectual property rights. All of these national and international intellectual property rules, however, will be worthless if not implemented properly. The examination of intellectual property rights protection in China and Pakistan is the aim of this research work. To illustrate and describe the variations in IPR protection assessments, this study also compares international IPR indicators of both countries. This study’s findings indicate significant differences between the IPR index and the final outcomes. All IPR indicators reveal that China has substantially done better than Pakistan in recent years, although outcomes range greatly from 2011 to 2022. The study recommends that policymakers should explore options for bilateral or multilateral cooperation in this field.